Bipolar composite current collector, preparation method thereof and solid-state lithium secondary battery

The bipolar composite fluid is prepared by magnetron sputtering and water electroplating and electroplating electrodeposition technology, and the roughening roller grinding treatment is used to solve the problems of insufficient adhesion and complex production processes in the prior art, and the high safety and high energy density of solid-state lithium secondary batteries are achieved.

CN119764463AActive Publication Date: 2025-04-04JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD

Patent Information

Application Number
CN202510020051.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-04
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing bipolar composite fluid collectors have shortcomings in adhesion and production process complexity, and have poor safety performance.

Method used

Bipolar composite fluids are prepared by magnetron sputtering and water electroplating and electroplating electrodeposition technology, and roughening roller grinding is used to improve adhesion, and the safety and production simplicity of the battery are improved by optimizing the structural design of polymer layer and metal layer.

Benefits of technology

The high safety, high energy density, long cycle life and environmental protection of bipolar composite fluids in solid-state lithium secondary batteries are achieved, simplifying the battery structure and production process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764463A_ABST
    Figure CN119764463A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a bipolar composite current collector, a preparation method thereof and a solid-state lithium secondary battery. Comprising the following steps: 1, adding polyethylene oxide and lithium bis (fluorosulfonyl) imide into N, N-dimethylformamide, carrying out vacuum drying at 80-100 DEG C for 10-14 hours, and cooling to obtain a solid polymer electrolyte; 2, sequentially adding a positive active material, a solid polymer electrolyte, a conductive agent and a binder into N-methyl pyrrolidone, and uniformly mixing and stirring to obtain positive slurry; and coating the outer surface of a metal Al layer of a bipolar composite current collector with the positive electrode material, and drying to obtain the positive electrode material. Taking the product as an intermediate product; winding or laminating the intermediate product; the solid-state lithium secondary battery composed of the bipolar composite current collector is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary batteries, in particular to a bipolar composite current collector and a preparation method thereof, and a solid-state lithium secondary battery. Background Art

[0002] With the continuous growth of the new energy vehicle market, the requirements for battery performance are increasing day by day, and composite current collectors in batteries as a new type of material have attracted much attention. Although composite current collectors have improved battery performance to a certain extent, bipolar current collectors are gradually becoming potential products in the future market due to their more excellent performance.

[0003] In the prior art, Adv. Funct. Mater. 2024, 34, 2310925 reported an ultra-light bipolar composite current collector. Although it achieved an ultra-light design, the adhesion between the metal layer and the insulating polymer film was insufficient, which resulted in the metal layer being easy to fall off under certain conditions. The production process was also relatively complicated and the safety performance was poor. CN202311349176.3 provided a new bipolar composite current collector and its preparation process, which had improved adhesion, but was not simple enough and had too much mass.

[0004] The solid-state polymer battery of the present invention adopts key technologies such as solid-state polymer electrolyte, negative electrode-free design, and optimized interface engineering in its composition, and exhibits advantages such as high safety, high energy density, long cycle life, environmental protection, and design flexibility.

[0005] Therefore, it is particularly necessary to prepare a solid-state lithium secondary battery composed of a bipolar composite current collector. Summary of the invention

[0006] The object of the present invention is to provide a bipolar composite current collector and a preparation method thereof, as well as a solid-state lithium secondary battery, so as to solve the problems raised in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a bipolar composite current collector comprises the following steps: Step 1: (1) magnetron sputtering a layer of alloy on one side of the polymer layer to form an intermediate alloy layer; sputtering a layer of aluminum metal seed layer on the intermediate alloy layer, and then electroplating aluminum to form a positive electrode metal layer to obtain a metal Al layer; (2) magnetron sputtering a layer of alloy on the other side of the polymer layer to form an intermediate alloy layer; sputtering a layer of copper metal seed layer on the intermediate alloy layer, and then electroplating copper to form a negative electrode metal layer to obtain a metal Cu layer; Step 2: The metal Al layer and the metal Cu layer are subjected to a roughening roller grinding process to obtain a bipolar composite current collector.

[0008] Preferably, the polymer layer is a polymer film of 1 to 15 μm; the material of the polymer film includes one or more of polyethylene terephthalate, polypropylene, polytetrafluoroethylene, polyimide, polyethylene, and polyethylene naphthalate; The intermediate alloy layer includes metal A and metal B; the metal A includes one of copper, silver, magnesium, aluminum, and indium; the metal B includes one of germanium, platinum, zinc, gold, tin, lead, cadmium, antimony, bismuth, gallium, carbon, silicon, and boron.

[0009] More optimally, the thickness of the metal Cu layer is 0.5-10 μm; the thickness of the metal Al layer is 1-20 μm; and the thickness of the intermediate alloy layer is 15-20 nm.

[0010] Furthermore, the metal alloy layer includes a copper-tin alloy layer with a mass ratio of 1-5:5-9.

[0011] More optimally, in the roughening roller grinding process, the roughening degree of the roughened roller pressed structure is 0.1-10 Ra, preferably 1-5 Ra.

[0012] More optimally, a bipolar composite current collector prepared by a preparation method of a bipolar composite current collector is characterized in that the structure of the bipolar composite current collector includes a metal Al layer, an intermediate alloy layer, a polymer layer, an intermediate alloy layer and a metal Cu layer from top to bottom.

[0013] More optimally, the bipolar composite current collector is applied to a solid-state lithium secondary battery; the structure of the solid-state lithium secondary battery comprises a solid polymer electrolyte, a positive electrode material, and a bipolar composite current collector from top to bottom.

[0014] Preferably, the method for preparing the solid-state lithium secondary battery comprises the following steps: Step 1: adding polyethylene oxide and bis(fluorosulfonyl)imide lithium salt to N,N-dimethylformamide, vacuum drying at 80-100° C. for 10-14 hours, and cooling to obtain a solid polymer electrolyte; Step 2: sequentially adding the positive electrode active material, the solid polymer electrolyte, the conductive agent, and the binder into N-methylpyrrolidone and mixing them evenly to obtain a positive electrode slurry; coating the positive electrode slurry on the outer surface of the metal Al layer of the bipolar composite current collector, and drying the positive electrode slurry to obtain a positive electrode material; this is used as an intermediate product; Step 3: The intermediate product is wound or stacked to obtain a solid-state lithium secondary battery.

[0015] More optimally, the molar ratio of polyethylene oxide to bis(fluorosulfonyl)imide lithium salt in the raw materials of the solid polymer electrolyte is 8-20:1; The raw materials of the positive electrode slurry include the following components: positive electrode active material, solid polymer electrolyte, conductive agent, and binder in a mass ratio of 6:2:1:1.

[0016] Preferably, the preparation method of the binder comprises the following steps: Step 1: (1) Add carboxymethyl guar gum and epoxy polyethylene glycol acrylate to 25-40% ethanol aqueous solution, add potassium hydroxide aqueous solution and ethyl phosphate, react at 60-80°C for 10-15 hours, purify, dry to obtain modified guar gum for later use; (2) Under nitrogen atmosphere, add 2,3,5,6-pyridinetetraamine trihydrochloride, ethyl isocyanate acrylate and dibutyltin dilaurate to xylene solvent, react at 70-80°C for 2-3 hours, filter, purify to obtain alkenyl pyridine for later use; Step 2: Add carboxymethyl cellulose, potassium persulfate and sodium sulfite to deionized water and react at 40-50°C for 60-90 minutes, add acrylamide, butyl methacrylate, modified guar gum and alkenyl pyridine, react at 40-50°C for 3-4 hours, add potassium hydroxide aqueous solution and react at 90-95°C for 60-90 minutes, then cool to 40-50°C, add disodium hydrogen phosphate and react for 3-4 hours, wash, precipitate and dry to obtain an adhesive.

[0017] More optimally, the raw materials of the adhesive include the following components: by mass, 5 to 6 parts of carboxymethyl cellulose, 0.2 to 0.6 parts of potassium persulfate, 0.2 to 0.6 parts of sodium sulfite, 50 to 60 parts of deionized water, 25 to 30 parts of acrylamide, 0.1 to 0.4 parts of butyl methacrylate, 4 to 5 parts of modified guar gum, 2 to 3 parts of alkenyl pyridine, 0.5 to 1 parts of potassium hydroxide aqueous solution, and 2 to 3 parts of disodium hydrogen phosphate.

[0018] More optimally, the raw materials of the modified guar gum include the following components: by mass, 7 to 8 parts of carboxymethyl guar gum, 6 to 7 parts of epoxy polyethylene glycol acrylate, 35 to 45 parts of 25 to 40% ethanol aqueous solution, 0.5 to 1 part of potassium hydroxide aqueous solution, and 2 to 3 parts of ethyl phosphate.

[0019] More optimally, the raw materials of the alkenyl pyridine include the following components: 7 to 8 parts by mass of 2,3,5,6-pyridinetetraamine trihydrochloride, 6 to 7 parts of ethyl isocyanate acrylate, 0.05 to 0.1 parts of dibutyltin dilaurate, and 35 to 45 parts of xylene solvent.

[0020] In the scheme, the number average molecular weight of the epoxy polyethylene glycol acrylate is 600-900.

[0021] Among them, guar gum is first modified to form a graft copolymer, and phosphoric acid groups and unsaturated groups are introduced to increase the migration channels of lithium ions and improve the lithium ion mobility; then multiple unsaturated bonds and pyridine groups are introduced through the reaction of amino groups and isocyanate. The pyridine group can increase the interaction force between molecules and improve the heat resistance and chemical stability of the binder. The unsaturated bonds can be used for subsequent polymerization reactions to form a hyperbranched structure, which helps to form more ion channels and is beneficial to the migration of lithium ions; the hyperbranched structure also reduces the linear arrangement of molecular chains and reduces the risk of thermal expansion; then a hyperbranched three-dimensional network structure is formed with polymer substances such as carboxymethyl cellulose and monomers such as acrylamide and butyl methacrylate to produce a synergistic effect, wherein the monomer improves its flexibility and water resistance, and the pores and channels in the three-dimensional network structure also provide more paths and channels for the migration of lithium ions, further improving the migration rate of lithium ions and the performance of the battery; the close arrangement of polymer chains and the formation of a cross-linked structure reduce the risk of thermal expansion. Finally, the phosphate group is introduced again, and the coordination bond formed with the lithium ions enhances the interaction between the binder and the positive electrode material, improves the bonding strength, and makes the electrode material more firmly attached to the current collector, thereby improving the cycle stability and service life of the battery.

[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The bipolar composite current collector can serve as the current collector for both the positive and negative electrodes, reducing the number of components, helping to simplify the battery structure, facilitating space utilization and battery design, and also improving the energy density of the battery.

[0023] 2. The process of preparing bipolar composite current collectors makes the battery preparation process relatively simple, less polluting, and able to achieve large-scale production. This helps to further reduce production costs and improve the market competitiveness of products.

[0024] 3. By preparing a bipolar composite current collector, it can be compatible with a variety of battery materials and systems. At the same time, it can also be used as a non-negative electrode material in a non-negative electrode lithium battery, which is beneficial to reduce the nucleation overpotential of lithium, achieve uniform deposition of lithium, and further improve the overall performance of the battery. In addition, due to its bipolarity, battery cells can be stacked, reducing the use of current collectors, negative electrode materials, and external packaging, which can greatly reduce costs and simplify the battery assembly process.

[0025] 4. The binder is composed of modified guar gum, carboxymethyl cellulose and other polymer compounds, forming a complex three-dimensional network structure, providing mechanical support, ensuring electrode stability, accommodating volume changes, and providing more paths for lithium ion migration, improving migration rate and battery performance. The pyridine structure and phosphate group interact strongly with lithium ions, promoting migration and improving battery performance. Unsaturated group grafting and branching enhance the compactness and stability of the network structure, improve strength, solvent resistance and thermal stability, while enhancing adhesion to electrode materials and improving battery cycle stability and service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram of the structure of a bipolar all-solid-state battery assembled with a bipolar composite current collector; Figure 2 A schematic diagram of the structure of a bipolar all-solid-state lithium secondary battery assembled with a bipolar composite current collector; Figure 3 This is a charge and discharge curve of a bipolar all-solid-state lithium secondary battery assembled with a bipolar composite current collector prepared in Example 4 and measured at room temperature and 0.1C. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Pre-preparation: The specific preparation process of the bipolar composite current collector is as follows: Step 1: (1) magnetron sputter a layer of alloy on one side of the polymer layer to form an intermediate alloy layer, set the power to 5 kW, the argon flow rate to 50 mL / min, the coating vacuum to 0.08 Pa, and the coating time to 1 s; then perform water electroplating to electro-deposit aluminum on the intermediate alloy layer to form a positive metal layer to obtain a metal Al layer; the specific process conditions are: the plating solution includes 100 g / L copper sulfate, 120 g / L sulfuric acid, 46 mg / L HCl (hydrochloric acid), 15 mg / L sodium 3-mercapto-1-propane sulfonate, 0.6 mg / L 2-mercaptopyridine, 100 mg / L polyethylene glycol (average molecular weight 10000), the temperature of the plating solution is 25 ° C, and the average cathode current density is 1.5 A / dm 2 , the electroplating time is 5 min; (2) magnetron sputtering a layer of alloy on the other side of the polymer layer to form an intermediate alloy layer; sputtering a layer of copper metal seed layer on the intermediate alloy layer, and then electroplating copper to form a negative electrode metal layer to obtain a metal Cu layer; Step 2: The metal Al layer and the metal Cu layer are set to a roughness of 1Ra and subjected to a roughening roller grinding treatment to obtain a bipolar composite current collector.

[0029] Embodiment 1: A solid-state lithium secondary battery, comprising the following steps: Referring to the above pre-preparation process, the prepared bipolar composite current collector is used in the battery assembly process. In the current collector of this embodiment, the polymer layer is a polyethylene terephthalate film with a thickness of 4.5 microns, the intermediate metal layer is a copper-tin alloy layer with a thickness of 15 nanometers, the positive electrode metal layer and the negative electrode metal layer are respectively an aluminum layer and a copper layer, the aluminum layer is 1 micron thick, and the copper layer is 0.5 micron thick. The positive electrode active material is lithium iron phosphate, and the electrolyte is polyethylene oxide. The process of assembling the battery is as follows: Step 1: adding polyethylene oxide and bis(fluorosulfonyl)imide lithium salt to N,N-dimethylformamide, the amount of polyethylene oxide and bis(fluorosulfonyl)imide lithium salt being 16:1, vacuum drying at 90° C. for 12 hours, and cooling to obtain a solid polymer electrolyte; Step 2: 60 parts of positive electrode active material, 20 parts of solid polymer electrolyte, 10 parts of conductive agent and 10 parts of binder are added to N-methylpyrrolidone in sequence and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is coated on the outer surface of the metal Al layer of the bipolar composite current collector and dried to obtain a positive electrode material; this is used as an intermediate product; Step 3: The intermediate product is wound or stacked to obtain a solid-state lithium secondary battery.

[0030] Embodiment 2: A method for preparing a bipolar composite current collector and a solid-state lithium secondary battery, comprising the following steps: Referring to the above pre-preparation process, the prepared bipolar composite current collector is used in the battery assembly process. In the current collector of this embodiment, the polymer material substrate layer is a polyethylene terephthalate film with a thickness of 4.5 microns, the intermediate metal layer is a copper-tin alloy layer with a thickness of 15 nanometers, the positive electrode metal layer and the negative electrode metal layer are respectively an aluminum layer and a copper layer, the aluminum layer is 2 microns thick, and the copper layer is 1 micron thick. The positive electrode active material is lithium iron phosphate, and the electrolyte is polyethylene oxide. The process of assembling the battery is as follows: Step 1: adding polyethylene oxide and bis(fluorosulfonyl)imide lithium salt to N,N-dimethylformamide, the amount of polyethylene oxide and bis(fluorosulfonyl)imide lithium salt being 16:1, vacuum drying at 90° C. for 12 hours, and cooling to obtain a solid polymer electrolyte; Step 2: 60 parts of positive electrode active material, 20 parts of solid polymer electrolyte, 10 parts of conductive agent and 10 parts of binder are added to N-methylpyrrolidone in sequence and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is coated on the outer surface of the metal Al layer of the bipolar composite current collector and dried to obtain a positive electrode material; this is used as an intermediate product; Step 3: The intermediate product is wound or stacked to obtain a solid-state lithium secondary battery.

[0031] Embodiment 3: A method for preparing a bipolar composite current collector and a solid-state lithium secondary battery, comprising the following steps: Referring to the above pre-preparation process, the prepared bipolar composite current collector is used in the battery assembly process. In the current collector of this embodiment, the polymer material substrate layer is a polyethylene terephthalate film with a thickness of 6 microns, the intermediate metal layer is a copper-tin alloy layer with a thickness of 15 nanometers, the positive electrode metal layer and the negative electrode metal layer are respectively an aluminum layer and a copper layer, the aluminum layer is 2 microns thick, and the copper layer is 1 micron thick. The positive electrode active material is lithium iron phosphate, and the electrolyte is polyethylene oxide. The process of assembling the battery is as follows: Step 1: adding polyethylene oxide and bis(fluorosulfonyl)imide lithium salt to N,N-dimethylformamide, the amount of polyethylene oxide and bis(fluorosulfonyl)imide lithium salt being 16:1, vacuum drying at 90° C. for 12 hours, and cooling to obtain a solid polymer electrolyte; Step 2: 60 parts of positive electrode active material, 20 parts of solid polymer electrolyte, 10 parts of conductive agent and 10 parts of binder are added to N-methylpyrrolidone in sequence and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is coated on the outer surface of the metal Al layer of the bipolar composite current collector and dried to obtain a positive electrode material; this is used as an intermediate product; Step 3: The intermediate product is wound or stacked to obtain a solid-state lithium secondary battery.

[0032] Embodiment 4: A method for preparing a bipolar composite current collector and a solid-state lithium secondary battery, comprising the following steps: Referring to the above pre-preparation process, the prepared bipolar composite current collector is used in the battery assembly process. In the current collector of this embodiment, the polymer material substrate layer is a polyethylene terephthalate film with a thickness of 4.5 microns, the intermediate metal layer is a copper-tin alloy layer with a thickness of 15 nanometers, the positive electrode metal layer and the negative electrode metal layer are respectively an aluminum layer and a copper layer, the aluminum layer is 1 micron thick, and the copper layer is 0.5 micron thick. The positive electrode active material is lithium iron phosphate, and the electrolyte is polyethylene oxide. The process of assembling the battery is as follows: Step 1: adding polyethylene oxide and bis(fluorosulfonyl)imide lithium salt to N,N-dimethylformamide, the amount of polyethylene oxide and bis(fluorosulfonyl)imide lithium salt being 16:1, vacuum drying at 90° C. for 12 hours, and cooling to obtain a solid polymer electrolyte; Step 2: 60 parts of positive electrode active material, 20 parts of solid polymer electrolyte, 10 parts of conductive agent and 10 parts of binder are added to N-methylpyrrolidone in sequence and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is coated on the outer surface of the metal Al layer of the bipolar composite current collector and dried to obtain a positive electrode material; this is used as an intermediate product; Step 3: The intermediate product is wound or laminated to obtain a solid-state lithium secondary battery; two solid-state battery cells are stacked so that the surfaces fit tightly together; finally, the compacted solid-state battery cells are encapsulated in a button battery to obtain a high-voltage bipolar all-solid-state battery.

[0033] Example 5: Based on Example 1, a branched binder is selected, and the rest remains unchanged, comprising the following steps: Referring to the above pre-preparation process, the prepared bipolar composite current collector is used in the battery assembly process. In the current collector of this embodiment, the polymer material substrate layer is a polyethylene terephthalate film with a thickness of 4.5 microns, the intermediate metal layer is a copper-tin alloy layer with a thickness of 15 nanometers, the positive electrode metal layer and the negative electrode metal layer are respectively an aluminum layer and a copper layer, the aluminum layer is 1 micron thick, and the copper layer is 0.5 micron thick. The positive electrode active material is lithium iron phosphate, and the electrolyte is polyethylene oxide. The specific preparation process is as follows: Step 1: (1) Add 7.5 parts of carboxymethyl guar gum and 6.5 parts of epoxy polyethylene glycol acrylate to 40 parts of 35% ethanol aqueous solution, add 0.8 parts of potassium hydroxide aqueous solution and 2.5 parts of ethyl phosphate, react at 70°C for 12 hours, purify, dry, and obtain modified guar gum for later use; (2) Under a nitrogen atmosphere, add 7.5 parts of 2,3,5,6-pyridinetetraamine trihydrochloride, 6.5 parts of isocyanate ethyl acrylate, and 0.08 parts of dibutyltin dilaurate to 40 parts of xylene solvent, react at 75°C for 2.5 hours, filter, and purify. , obtain alkenyl pyridine for standby use; (3) add 5.5 parts of carboxymethyl cellulose, 0.3 parts of potassium persulfate, and 0.3 parts of sodium sulfite to 55 parts of deionized water, react at 45°C for 75 minutes, add 28 parts of acrylamide, 0.3 parts of butyl methacrylate, 4.5 parts of modified guar gum, and 2.5 parts of alkenyl pyridine, react at 45°C for 3.5 hours, add 0.8 parts of potassium hydroxide aqueous solution, react at 92°C for 75 minutes, then cool to 45°C, add 2.5 parts of disodium hydrogen phosphate, react for 3.5 hours, wash, precipitate, and dry to obtain an adhesive; Step 2: adding polyethylene oxide and bis(fluorosulfonyl)imide lithium salt to N,N-dimethylformamide, the amount of polyethylene oxide and bis(fluorosulfonyl)imide lithium salt being 16:1, vacuum drying at 90° C. for 12 hours, and cooling to obtain a solid polymer electrolyte; Step 3: 60 parts of positive electrode active material, 20 parts of solid polymer electrolyte, 10 parts of conductive agent and 10 parts of binder are added to N-methylpyrrolidone in sequence and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is coated on the outer surface of the metal Al layer of the bipolar composite current collector and dried to obtain a positive electrode material; this is used as an intermediate product; Step 4: The intermediate product is wound or stacked to obtain a solid-state lithium secondary battery.

[0034] Comparative Example 1: Based on Example 1, the roughening degree is set to 0.05Ra and a roughening roller grinding process is performed, and the remaining specific steps are the same as those in Example 1.

[0035] Comparative Example 2: Based on Example 5, alkenyl pyridine was not added, and the remaining specific steps were the same as Example 5.

[0036] Performance test: The prepared solid-state lithium secondary battery composed of a bipolar composite current collector was subjected to constant current charge and discharge tests in the voltage range of 2.7~3.8 V using a NEWARE battery test system. The discharge specific capacity was tested at room temperature at 0.1C (1C is 170mAh / g), and the capacity retention rate after 200 cycles was recorded. The data obtained are shown in Table 1 below:

[0037] Conclusion: The bipolar composite current collector prepared in this paper can be used as the current collector of both the positive and negative electrodes, thereby improving the energy density of the battery; the preparation of the bipolar composite current collector makes the battery process simpler and less polluting, which is conducive to large-scale production and reduces costs; the current collector is compatible with a variety of battery materials and can be used as a negative electrode-free material, reducing costs and simplifying assembly; a binder composed of a polymer compound is prepared to promote lithium ion migration, enhance the compactness and stability of the network structure, and improve the battery cycle stability and service life.

[0038] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a bipolar composite current collector, characterized in that: The following steps are involved: Step 1: (1) magnetron sputtering a layer of alloy on one side of the polymer layer to form an intermediate alloy layer; sputtering a layer of aluminum metal seed layer on the intermediate alloy layer, and then electroplating aluminum to form a positive electrode metal layer to obtain a metal Al layer; (2) magnetron sputtering a layer of alloy on the other side of the polymer layer to form an intermediate alloy layer; sputtering a layer of copper metal seed layer on the intermediate alloy layer, and then electroplating copper to form a negative electrode metal layer to obtain a metal Cu layer; Step 2: The metal Al layer and the metal Cu layer are subjected to a roughening roller grinding process to obtain a bipolar composite current collector.

2. The method for preparing a bipolar composite current collector according to claim 1, characterized in that: The polymer layer is a polymer film of 1 to 15 μm; the material of the polymer film includes one or more of polyethylene terephthalate, polypropylene, polytetrafluoroethylene, polyimide, polyethylene, and polyethylene naphthalate; The intermediate alloy layer includes metal A and metal B; the metal A includes one of copper, silver, magnesium, aluminum, and indium; the metal B includes one of germanium, platinum, zinc, gold, tin, lead, cadmium, antimony, bismuth, gallium, carbon, silicon, and boron.

3. The method for preparing a bipolar composite current collector according to claim 1, characterized in that: The thickness of the metal Cu layer is 0.5-10 μm; the thickness of the metal Al layer is 1-20 μm; and the thickness of the intermediate alloy layer is 15-20 nm.

4. The method for preparing a bipolar composite current collector according to claim 1, characterized in that: In the roughening roller grinding process, the roughening degree of the metal after the roughening roller grinding process is 0.1~10Ra.

5. The bipolar composite current collector prepared by the method for preparing a bipolar composite current collector according to any one of claims 1 to 4, characterized in that: The structure of the bipolar composite current collector comprises, from top to bottom, a metal Al layer, an intermediate alloy layer, a polymer layer, an intermediate alloy layer and a metal Cu layer.

6. A solid-state lithium secondary battery, characterized in that: The bipolar composite current collector of claim 5 is applied to a solid-state lithium secondary battery; the structure of the solid-state lithium secondary battery comprises a solid polymer electrolyte, a positive electrode material, and a bipolar composite current collector from top to bottom.

7. A solid-state lithium secondary battery according to claim 6, characterized in that: The preparation method of the solid-state lithium secondary battery comprises the following steps: Step 1: adding polyethylene oxide and bis(fluorosulfonyl)imide lithium salt to N,N-dimethylformamide, vacuum drying at 80-100° C. for 10-14 hours, and cooling to obtain a solid polymer electrolyte; Step 2: sequentially adding the positive electrode active material, the solid polymer electrolyte, the conductive agent, and the binder into N-methylpyrrolidone and mixing them evenly to obtain a positive electrode slurry; coating the positive electrode slurry on the outer surface of the metal Al layer of the bipolar composite current collector, and drying the positive electrode slurry to obtain a positive electrode material; this is used as an intermediate product; Step 3: The intermediate product is wound or stacked to obtain a solid-state lithium secondary battery.

8. A solid-state lithium secondary battery according to claim 7, characterized in that: The molar ratio of polyethylene oxide and bis(fluorosulfonyl)imide lithium salt in the raw materials of the solid polymer electrolyte is 8-20:1; The raw materials of the positive electrode slurry include the following components: positive electrode active material, solid polymer electrolyte, conductive agent, and binder in a mass ratio of 6:2:1:

1.

9. A solid-state lithium secondary battery according to claim 8, characterized in that: The preparation method of the binder comprises the following steps: Step 1: (1) Add carboxymethyl guar gum and epoxy polyethylene glycol acrylate to 25-40% ethanol aqueous solution, add potassium hydroxide aqueous solution and ethyl phosphate, react at 60-80°C for 10-15 hours, purify, dry to obtain modified guar gum for later use; (2) Under nitrogen atmosphere, add 2,3,5,6-pyridinetetraamine trihydrochloride, ethyl isocyanate acrylate and dibutyltin dilaurate to xylene solvent, react at 70-80°C for 2-3 hours, filter, purify to obtain alkenyl pyridine for later use; Step 2: Add carboxymethyl cellulose, potassium persulfate and sodium sulfite to deionized water and react at 40-50°C for 60-90 minutes, add acrylamide, butyl methacrylate, modified guar gum and alkenyl pyridine, react at 40-50°C for 3-4 hours, add potassium hydroxide aqueous solution and react at 90-95°C for 60-90 minutes, then cool to 40-50°C, add disodium hydrogen phosphate and react for 3-4 hours, wash, precipitate and dry to obtain an adhesive.

10. A solid-state lithium secondary battery according to claim 9, characterized in that: The raw materials of the adhesive include the following components: by mass, 5-6 parts of carboxymethyl cellulose, 0.2-0.6 parts of potassium persulfate, 0.2-0.6 parts of sodium sulfite, 50-60 parts of deionized water, 25-30 parts of acrylamide, 0.1-0.4 parts of butyl methacrylate, 4-5 parts of modified guar gum, 2-3 parts of alkenyl pyridine, 0.5-1 parts of potassium hydroxide aqueous solution, and 2-3 parts of disodium hydrogen phosphate.

Citation Information

Patent Citations

  • Lithium ion battery, bipolar current collector and manufacturing method of bipolar current collector

    CN113270589A

  • High-voltage PEO-based solid electrolyte and preparation method and application thereof

    CN115995603A

  • Ionic copolymer binder as well as preparation method and application thereof

    CN117219775A

  • Aqueous binder for negative electrode material of non-aqueous secondary battery, preparation method and application

    CN117264578A

  • Novel bipolar composite current collector and preparation process thereof

    CN117423838A

Cited By

  • Novel bipolar composite current collector and preparation process thereof

    CN117423838A